Implementasi Sequence of Service Dalam Memberikan Pelayanan Kepada Tamu Di Urbanview MJ Hotel Syariah Cirebon By RedDoorz - Ana Septaqiani; Ridwan Widagdo; Alvien Hariesma (i-Tourism: Jurnal Pariwisata Syariah, 2026)
The Sharia-based hospitality industry in Indonesia continues to grow alongside the increasing number of Muslim tourists and Muslim-friendly destinations. However, some Sharia hotels do not consistently apply Islamic service standards, which negatively impacts the guest experience. It is crucial for these hotels to align their operations with Sharia principles to enhance Muslim guest satisfaction. This study employs a descriptive qualitative method, with data collected through interviews and direct observation. It examines how hotel staff execute the service sequence and how guests perceive the service experience during their stay, as well as the factors that support or hinder service delivery in accordance with Sharia principles. A literature review further supports this study using various reliable sources. The findings indicate that Urbanview MJ Hotel Syariah Cirebon by RedDoorz effectively implement the sequence of service from pre-arrival through check-out while adhering to rules consistent with Sharia values such as shiddiq, amanah, ihsan, and adil. The services provided create a sufficiently satisfying stay experience for guests due to efficient booking processes and responsive staff. Although this hotel promotes a culture of tolerance without requiring staff to use Islamic greetings when welcoming guests, challenges such as limited facilities and varying levels of guest knowledge still remain. Continuous improvement is needed to enhance service quality and guest satisfaction.